Redefining The Road Ahead in The Sharing Economy: How to Build Sustainable Competitive Advantage of Ride-Hailing Services - Putra, Wawas Bangun Tegar Sunaryo; Harista, Fransisca Vania; Kurniawan, Nathassya (Politeknik Negeri Bengkalis, 2024)
The sharing economy's ride-hailing sector is marked by fierce competition and continuous innovation. This study investigates the competitive dynamics of this industry, focusing on the role of market dynamics, promotional innovation, and operational agility in establishing a sustainable competitive advantage (SCA). Despite an extensive review of 2,192 sources from 2010 to 2022, a significant gap was identified, with minimal focus on SCA within ride-hailing. The research methodology encompassed a comprehensive literature review, identifying only one out of 1,099 publications that directly addressed SCA in the ride-hailing context. Building on this gap, the study developed a novel conceptual framework that emphasizes market awareness, innovative engagement strategies, and operational flexibility as key components for maintaining a competitive edge.The proposed model highlights the importance of stakeholder engagement, the identification of growth catalysts, and the navigation of industry-specific challenges. This framework aims to enhance the understanding of SCA in ride-hailing and suggests pathways for companies to achieve leadership in sustainability.This study contributes to the discourse on sustainable business management by proposing a strategic approach for ride-hailing companies to secure and sustain a competitive advantage. It underscores the necessity of innovative and flexible operational strategies in responding to market dynamics and stakeholder expectations. Future research is encouraged to explore the untapped sustainable capacities of the ride-hailing sector, further enriching the strategies for achieving long-term success and sustainability in this competitive landscape.